A Characterization of the Cyclic Groups by Subgroup Indices. (1st January 2016) - Oman, Greg; Slattum, Victoria
Summary: We provide a new characterization of cyclic groups using the index of a subgroup. We show that a group, finite or infinite, is cyclic exactly when its distinct subgroups have distinct indices.